2013
DOI: 10.1088/0953-2048/26/11/114004
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and irreversible mechanical effects in real cable-in-conduit conductors

Abstract: The strong strain sensitivity of the critical properties of Nb 3 Sn is well established. However, the roles played by both the reversible strain sensitivity and the susceptibility to brittle fracture of Nb 3 Sn filaments is still leading to unexpected results and resulting design modifications of conductors. Practical conductors require acceptance of less than perfect superconducting behaviour because such conductors actually operate continuously in a slightly resistive mode. Performance testing of the ITER co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
(45 reference statements)
2
36
0
Order By: Relevance
“…Both the compressive and tensile tails of the strain distribution depress T cs : the compressive tail via reversible reduction, while the tensile tail via irreversible reduction of I c . Which tail has the major effect in TF conductors is still debated, see for example the exhaustive review in [13]. Filament breakage is often considered responsible of reduction of T cs during cycling, but in [14] and [15] it was shown that the broadening of the strain distribution alone (without including breakage) can result in T cs reduction during cycling and low n values which were in agreement with the measurements.…”
Section: Strain In Iter Cicsupporting
confidence: 54%
See 2 more Smart Citations
“…Both the compressive and tensile tails of the strain distribution depress T cs : the compressive tail via reversible reduction, while the tensile tail via irreversible reduction of I c . Which tail has the major effect in TF conductors is still debated, see for example the exhaustive review in [13]. Filament breakage is often considered responsible of reduction of T cs during cycling, but in [14] and [15] it was shown that the broadening of the strain distribution alone (without including breakage) can result in T cs reduction during cycling and low n values which were in agreement with the measurements.…”
Section: Strain In Iter Cicsupporting
confidence: 54%
“…The margin of improvement is basically two to three times larger than the reduction observed after 1000 electromagnetic cycles in TF conductors. [12] and [13]) are also reported. The dashed lines are for hypothetical conductors made with the same strands but working at effective strain of -0.37%, -0.2% and 0% .…”
Section: Evaluating the Margin Of Improvementmentioning
confidence: 89%
See 1 more Smart Citation
“…Here, D stands for the diameter of the strand. If the maximum strain is larger than 1%, the strand would be considered as cracking [10,[24][25][26]. Based on these equations, the coefficient a ij can be calculated, as well as the buckling deflection, the relationship between the radius of curvature, and the thermal compression strain ε Thermal or slid strainε Slid .…”
Section: Rotation Analysis Of the Ciccmentioning
confidence: 99%
“…This method is applied to a commercial MgB2 strand. The constitutive equations are built for future use in multi-scale finite element simulations to predict the mechanical behavior [15] or the electrical behavior [16], [17].…”
Section: Introductionmentioning
confidence: 99%